EFEKTIFITAS PELATIHAN PNEUMATIK DALAM MENINGKATKAN KOMPETENSI SISWA JURUSAN PERMESINAN DI SMK PGRI JATIBARANG - Kusmayadi, Adi; Irawan, Candra; Farhan, Ahmad; Alba Pradhana , Claudha (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2024)
The development of automation technology in modern industry demands an increase in technical competence for vocational students, particularly in the field of pneumatics. The widespread application of pneumatic systems in industrial processes makes mastering this technology essential for students in the machinery department. This study aims to assess the effectiveness of pneumatic system training for Machinery Department students at the Vocational High School (SMK) PGRI Jatibarang in enhancing their knowledge and skills. The method used in this research is a quasi-experimental design with a pre-test and post-test format. Students were provided with theoretical materials, guidance, and hands-on practice on pneumatic equipment. The analysis results show an average N-Gain of 0.863, which falls into the high improvement category, indicating that this training significantly impacts students' understanding of pneumatic systems. The implications of this research suggest that practice-based training and material reinforcement can serve as effective strategies in vocational education to prepare students for industry demands, emphasizing the importance of hands-on approaches in technical skills learning.